Managing stress during the COVID-19 pandemic: The application of deep breathing relaxation technique and diary feedback among students - Zahra, Yunita; Dewi, Ika Sari; Meutia, Amalia; Nazriani, Dina; Siregar, Suri Mutia; Burhan, Omar K. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Having to stay at home and disconnected from their social world during the Covid-19 lockdown is stressful for many people, including students. The current paper reports the application of a deep breathing relaxation technique among students from the Faculty of Psychology Universitas Sumatera Utara, to regulate their stress levels at home. Twenty-five students participated in this intervention program. We trained them in a deep breathing relaxation technique and asked them to practice the technique twice a day, in the morning and the evening. We followed their progress for five consecutive days, in which participants filled a stress diary twice a day, in the morning and the evening. Based on the diary, a feedback by a psychologist was sent to each individual participant the next day. We assessed the effectiveness of the intervention program by comparing the students' perceived stress at the pre-intervention phase compared to their stress level at the post-intervention phase. The results showed a significant and meaningful impact of the intervention program, in which students reported lower perceived stress at the post-intervention compared to the pre-intervention phase.